Optimization of EDXRF for the study of heavy metal pollution of Lake Victoria - Mahommed, NK; Makundi, IN (Tanzania Journal of Science, 2021)
This study reports on the optimisation and calibration of the Energy Dispersive X-ray Fluorescence (EDXRF) spectrometer installed in the Department of Physics, University of Dar es Salaam. The spectrometer was subsequently utilized to determine concentrations of heavy metals in water hyacinth (Eichhornia crassipes (Mart) Solms.) found growing along the shore of Lake Victoria. The optimal conditions and detection limits were determined experimentally by variation of the excitation parameters. The study found that the use of a collimator with two apertures of diameter 4 mm each placed 8 mm apart and made of materials that do not interfere with elements to be determined from the samples, gave lowest detection limits. The optimal pairing of voltage and current was found to be 40 kV and 30 mA while measuring time was 2000 seconds. Roots of the water hyacinth were used in experiments to check the validity and sensitivity of the equipment. The water plants were collected from areas influenced by industrial and domestic seqage around Mwanza town, namely Mwanza South, Mwanza Central and Mwanza North. Mwanza North had quite a few industries and human settlements. The samples were each oven-dried, ground into a fine powder and pressed into a pellet. Water hyacinth from the industrial area and those from sewage discharge points were found to have higher concentrations of heavy metals (K, Ca, Sc, Ti, Mn, Fe, Co, Ni, Zn and Pb) than those from non polluted area. A more detailed study, involving more samples, is needed in order to be able to statistically quantify the differences.